2018
DOI: 10.1007/s10561-018-9732-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transforming growth factor-β2 on biological regulation of multilayer primary chondrocyte culture

Abstract: Cytokines are extremely potent biomolecules that regulate cellular functions and play multiple roles in initiation and inhibition of disease. These highly specialised macromolecules are actively involved in control of cellular proliferation, apoptosis, cell migration and adhesion. This work, investigates the effect of transforming growth factor-beta2 (TGF-β2) on the biological regulation of chondrocyte and the repair of a created model wound on a multilayer culture system. Also the effect of this cytokine on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…TGF-β2 has previously been shown to negatively mediate the growth of physiological chondrocytes ( 28 , 29 ) and human chondrosarcoma cells ( 30 ). In the present study, treatment of the HTB94 cells with TGF-β2 resulted in a potent decrease in growth (P≤0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β2 has previously been shown to negatively mediate the growth of physiological chondrocytes ( 28 , 29 ) and human chondrosarcoma cells ( 30 ). In the present study, treatment of the HTB94 cells with TGF-β2 resulted in a potent decrease in growth (P≤0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these findings indicated that the role of TGF-β2 in promoting cartilage defect repair was very important. On the contrary, Khaghani et al 96 indicated that TGF-β2 repressed the wound healing process of chondrocytes by scratch assay. This meant that TGF-β2 might have a negative regulatory effect on chondrocyte migration.…”
Section: The Basal Role Of Tgf-β2 In Chondrocyte Life Cyclementioning
confidence: 96%
“…Interestingly, in recent studies, TGF-β2 had a negative effect on cell proliferation. For instance, Khaghani et al 96 showed that TGF-β2 exerted an inhibitory effect on chondrocyte cell proliferation and might have synergistic effects on joint chondrocytes with other growth factors or proteins, such as basic fibroblast growth factor (bFGF). 97 Moreover, cyclin B2 (the onset of proliferation) and proliferating cell nuclear antigen (PCNA) are regarded as proliferation markers.…”
Section: The Basal Role Of Tgf-β2 In Chondrocyte Life Cyclementioning
confidence: 99%
“…The TGF-β superfamily includes three isoforms, TGF-β1, -β2, and -β3, coded by genes with different locations in various chromosomes [86]. TGF-β are soluble extracellular proteins, which regulate the development in both vertebrates and invertebrates [87]. TGF-α belongs to the EGF family; it is a 50-amino-acid polypeptide, which in humans has 10 members, isolated from a conditioned medium of virally transformed cells and tumor cells [88].…”
Section: Transforming Growth Factor-beta Family and Wound Healingmentioning
confidence: 99%
“…TGF-α belongs to the EGF family; it is a 50-amino-acid polypeptide, which in humans has 10 members, isolated from a conditioned medium of virally transformed cells and tumor cells [88]. TGF-β members regulate cell functions such as migration, apoptosis, proliferation, and differentiation [87]. TGF-β is secreted in a latent form by most cells and is activated via TGF-β receptor signaling [89].…”
Section: Transforming Growth Factor-beta Family and Wound Healingmentioning
confidence: 99%